Effects of inductive methods on dunging behavior of weaning pigs in slatted floor pens - Yu, Wang; Dapeng, Li; Xiong, Shen; Zhengxiang, Shi (International Journal of Agricultural and Biological Engineering, 2016)
The excreta of pig is generally utilized to induce pigs to excrete in particular area, which reduces the subsequent work required to clean pens. This paper discussed a new induction device design based on the biological characteristics of pigs. Using different induction materials in the devices, the frequency and location of the excretory behavior of pigs through five treatments and a control group were compared. According to the results, different induction methods had significant (p<0.05) effects on frequency and duration of excretory behavior. Compared to the conventional induction method, the induction devices were significantly (p<0.05) more effective in training pigs to excrete in the assigned area, the most effective material used in the induction devices was feces. If the inductive feces had been preserved in the air for a longer time, the effect of inducing excretory behavior would have been more obvious. Empty devices did not work to induce pigs to excrete in the induction area. Keywords: animal behavior, weaning pigs, slatted floor pen, pig training, excretory behavior, inductive material DOI: 10.3965/j.ijabe.20160904.2560 Citation: Wang Y, Li D P, Shen X, Shi Z X. Effects of inductive methods on dunging behavior of weaning pigs in slatted floor pens. Int J Agric & Biol Eng, 2016; 9(4): 192－198.